Phase transition and aggregation behaviour of an UCST-type copolymer poly(acrylamide-co-acrylonitrile) in water: effect of acrylonitrile content, concentration in solution, copolymer chain length and presence of electrolyte. Issue 3 (20th December 2016) - Asadujjaman, Asad; Kent, Ben; Bertin, Annabelle
Abstract : We propose a model for the temperature-induced aggregation behaviour of UCST-type poly(acrylamide- co -acrylonitrile) copolymer in aqueous solution on the basis of turbidity measurements, SLS, DLS, SANS and cryo-TEM. Abstract : An UCST-type copolymer of acrylamide (AAm) and acrylonitrile (AN) (poly(AAm- co -AN)) was prepared by reversible addition fragmentation chain transfer (RAFT) polymerization and its temperature-induced phase transition and aggregation behaviour studied by turbidimetry, static and dynamic light scattering, small angle neutron scattering (SANS) and cryo-transmission electron microscopy (cryo-TEM) measurements. The phase transition temperature was found to increase with increasing AN content in the copolymer, concentration of the solutions and copolymer chain length. A significant effect was observed onto the phase transition temperature by addition of different electrolytes into the copolymer solution. The copolymer chains were aggregated below the phase transition temperature and disaggregated above it. The size of the aggregates increases with increasing AN contents and concentration of the copolymer solutions below the phase transition temperature. The copolymer chains were expanded and weekly associated in solution above the phase transition temperature. A model is proposed to explain such association–aggregation behaviour of poly(AAm- co -AN) copolymers depending on AN contents and concentration of the copolymer solutions as a function of temperature.